TRADISI BUDAYA NGABEN DAN PENEGMBANGAN PARIWISATA BERKELANJUTAN DI BALI - Intan, Aulia; Septiani, Amanda (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
The Ngaben ritual is a unique and meaningful cultural expression in Bali. This study analyzes the potentials and challenges of developing cultural tourism through the Ngaben tradition in Bali. Results indicate that Ngaben has significant potential as a cultural tourist attraction but faces challenges like commercialization and cultural preservation. This research proposes sustainable cultural tourism development strategies respecting local values. Until now, tourism as an economic activity has penetrated the realm of ritual and spirituality. Ngaben is a ritual procession that has a religious aspect. Ngaben is a promise of devotion (Swadharma) to each Prisentana which is associated with the Dharma Bhakti of children and family. Each stage of the ritual includes different offerings, as well as other equipment for the corpse. The stages of the ritual carried out are: handling the corpse (bathing, changing/dressing), ngaben, nyeka, ngarora, and purification.